FFD532 : Alternative Filmmaking / College of Creative Arts - UiTM, College of Creative Arts (Universiti Teknologi MARA (UiTM), 2020)
This course provides an overview of the important elements in alternative filmmaking. This course explores the history of alternative cinema from the Early European Avant-Garde Films to Southeast Asian Alternative Films, to understand the context of their development as a subversive cinema. This course also aims the students to create their own short alternative film to emancipate them from traditional and mass market entertainment, inviting the students to think differently and independently with other perspectives.